A Short Generalized Proof of Infinitude of Primes. (1st January 2022) - Mehta, Jay
Summary: In this article, we present a very short proof of infinitude of primes. This generalized proof is based on the idea of factorization of the product of primes and it unifies three proofs, the famous proof due to Euclid, a proof of Métrod, and the one due to Stieltjes.